(untitled) (Ameghiniana, 2018)
Ostracods have been recovered from the upper levels of the Pachaco Facies of the Tambolar Formation of the Argentine Precordillera. Four species, two of which are new (Bollia sp. nov., Neothlipsura khiska sp. nov.), are described. An evaluation of the conodont fauna suggests an late Silurian (Pridoli) to possibly Early Devonian (earliest Lochkovian) age for the unit. The ostracod fauna is characterized by the absence of dimorphic Palaeocopina, forms typically abundant during the Silurian, and by the presence of Tricornina, a thin shelled spinose genus, together with representatives of Binodicopina and Metacopina (Thlipsuroidea). The taxonomic composition of the ostracods corresponds to the Assemblage III of the Eifelian Mega-Assemblage or to a “mixed assemblage”, suggesting a deep subtidal environment close to the area of the storm wave base. This interpretation is consistent with an external platform environment proposed by other authors based on a stratigraphic analysis. The presence of ostracod taxa such as Neothlipsura khiska sp. nov. and Tricornina? sp. suggests a faunal link with the palaeocontinent of Laurentia.